Comparing the recovery of richness, structure, and biomass in naturally regrowing and planted reforestation. Issue 2 (28th November 2019) - Staples, Timothy L.; Mayfield, Margaret M.; England, Jacqueline R.; Dwyer, John M.
Abstract : The clearing of natural vegetation for agriculture has reduced the capacity of natural systems to provide ecosystem functions. Ecological restoration can restore desirable ecosystem functions, such as creating habitat for animal conservation and carbon sequestration as woody biomass. In order to maintain these beneficial ecosystem functions, restoration projects need to mature into self‐perpetuating communities. Here we compared the ecological attributes of two types of restoration, "active" tree plantings with "passive" natural forest regeneration ("natural regrowth") to existing remnant vegetation in a cleared agricultural landscape. Specifically, we measured differences between forest categories in factors that may predict future restoration failure or ecosystem collapse: aboveground plant biomass and biomass accrual over time (for regrowing stands), plant density and size class distributions, and diversity of functional groups based on seed dispersal and growth strategy traits. We found that natural regrowth and planted forests were similar in many ecological characteristics, including biomass accrual. Despite this, planted stands contained fewer tree recruit and shrub individuals, which may be due to limited recruitment in plantings. If this continues, these forests may be at risk of collapsing into nonforest states after mature trees senesce. Lower shrub density and richness of mid‐story trees may lead to lower structural complexity in planting plots, and alongside lower richness of fleshy‐fruited plant species may reduce animal resources and animal use of the restored stand. In our study region, natural regrowth may result in restored woodland communities with greater conservation and carbon mitigation value.